Autoimmune Neuromuscular Diseases Induced by Immunomodulating Drugs. Issue 1 (September 2018) - Supakornnumporn, Songkit; Katirji, Bashar
Abstract : Abstract: Immunomodulating drugs are widely used in autoimmune, transplant, and cancer patients. However, these drugs are associated with various autoimmune neuromuscular diseases such as demyelinating polyneuropathy, myasthenia gravis, and myositis. Early recognition of these complications and immediately terminating these drugs are very essential since some are life-threatening conditions. This review provides a general overview of drug-induced autoimmunity and autoimmune neuromuscular diseases associated with tumor necrosis factor alpha (TNF-α) antagonists, immune checkpoint inhibitors, and interferon (IFN) type 1 (IFN-β and IFN-α).